Electrostatic Field Calculations for Liquid Nitrogen Gaps Assuming a Decisive Field Factor - Stefan Fink (International Journal of Applied Power Engineering (IJAPE), 2018)
Volume effect on breakdown voltage is well known in high voltage engineering. The breakdown voltage behavior of liquid nitrogen depending on a high field volume had been quantitatively described for gap lengths up to 20 mm. Breakdown curves for longer gap lengths up to 96 mm derived from measurements with a facility “Fatelini 2” show oscillations and partly low withstand voltages. Electrostatic field calculation for such long gaps shows remarkable high field volume differences between a model for ideal sphere and models including fixation rods. Calculation for the used setup does not show monotonically increasing high field volume depending on gap length but a maximum around 60 mm which can explain the special breakdown behavior in a “mid range” gap length. Further high field calculations were done for not yet used setups in order to make considerations, e.g. for the influence of cryostat material or diameter.